Alteration of Influencing Factors of e-Learning Continued Intention for Different Degrees of Online Participation - Chang, Chi-Cheng; Liang, Chaoyun; Shu, Kuen-Ming; Chiu, Yi-Chun (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
The purpose of the present study was to investigate the variation of influencing factors of for different degrees of participation and to examine moderating effects of degrees of participation on influencing factors of e-learning continuance intention. Participants included 670 learners from an adult professional development website. Data was collected based on questionnaires and analyzed by Structural Equation Modeling (SEM). The Revised Information System Success Model proposed by DeLone and McLean and Innovation Adoption Theory of Rogers were in the present study. A research model including two constructs (curriculum and system as well as innovation adaptation) and eight influencing factors were proposed in the present study based on features of e-learning. The results revealed that the factors in the construct of curriculum and system could be varied for different degrees of learner participation. Among those factors, system quality and online interaction were the factors for the differences between low and high groups of participation. Furthermore, the factors in the construct of innovation adaptation could be varied for different degrees of participation. Among those factors, compatibility was the factor for the differences between low and high groups of participation. Degree of online participation demonstrated moderating effects on the influences of online interaction, relative advantage and compatibility in e-learning continuance intention.